Concentração de flúor em águas engarrafadas comercializadas no município de São Paulo - Grec, Roberto Henrique da Costa; Moura, Patrícia Garcia de; Pessan, Juliano Pelim [UNESP]; Ramires, Irene; Costa, Beatriz; Buzalaf, Marília Afonso Rabelo (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 2008)
O objetivo do estudo foi avaliar a concentração de flúor na água engarrafada comercializada, comparando-a aos valores impressos no rótulo da embalagem. Foram coletadas 229 amostras de água das 35 marcas disponíveis em diversos supermercados, mercearias e lanchonetes de grande circulação nas diferentes regiões do município de São Paulo, em 2006. A concentração de flúor foi determinada por análise em duplicata, utilizando o eletrodo íon-específico. A concentração de flúor variou entre 0,01 e 2,04 mg/l, com diferenças significantes entre os valores estipulados nos rótulos e os encontrados com a análise. Esses resultados reforçam a importância do controle dos níveis de flúor na água engarrafada por parte da vigilância sanitária.

The objective of the study was to evaluate the fluoride concentration in bottled water available on the market, in comparison with the values printed on the bottle label. Two hundred and twenty-nine water samples were collected from 35 brands available in several supermarkets, grocery stores and snack bars with high turnover in different regions of the municipality of São Paulo, Southeastern Brazil, in 2006. Fluoride concentrations were determined by duplicate analysis using an ion-specific electrode. The fluoride concentrations ranged from 0.01 to 2.04 mg/l, with significant differences between the values stipulated on labels and those found in the analyses. These results emphasize the importance of controls over fluoride levels in bottled water enforced by the sanitary surveillance agency.
Fluoride concentration in bottled water on the market in the municipality of São Paulo
Keywords: Água engarrafada; Compostos de flúor; Rotulagem de produtos; Alimentos e bebidas; Vigilância sanitária; Bottled water; Fluorine compounds; Product labeling; Food and beverages; Health surveillance